Artificial Intelligence (AI) as a Digital Strategy for National Defence in the Era of Global Politics - Susilowati, Ida; Nadirah, Kamilia; Lasampa, Aanisah Aprilia (UIN Jakarta, 2024)
Artificial Intelligence (AI) has become an important factor in crafting a country's defence strategy in the face of increasingly complex global political dynamics. This article reviews the country's efforts in applying AI in the context of defence strategy and digital politics. AI has helped countries analyse complex data, predict political changes and formulate more effective diplomacy strategies. Artificial Intelligence (AI) is now a state priority that is starting to be developed and continues to increase around the world, including as a defence effort in the military and non-military fields. This research is a type of qualitative research by applying descriptive analytical methods and literature study data analysis techniques. The findings of our research are that AI can analyse global political data from various sources. AI can be used to analyse public policy data and provide recommendations to political leaders about steps that might be taken. One of the implementations of AI in global politics is in facilitating collaboration between countries in facing global challenges by answering complex problems such as climate change, cyber security and cooperation between countries.